Changes in cholesterol metabolism during acute upper gastrointestinal bleeding: liver cirrhosis and non cirrhosis compared - Hrabovsky, Vladimir; Blaha, Vladimir; Hyspler, Radomir; Ticha, Alena; Skrobankova, Martina; Svagera, Zdenek (Biomedical papers, 2019)
Background: Cholesterol is derived via de novo synthesis and dietary absorption. Both processes can be monitored by determination of non-cholesterol sterol concentrations (lathosterol for synthesis; sitosterol and campesterol for absorption). The hypocholesterolemia that occurs during acute illness is a result of a multifactorial inability to compensate for the increased needs for this metabolite. The aim of this study was to examine the plasma cholesterol profile and both processes of cholesterol acquisition during acute upper gastrointestinal haemorrhage with emphasis on liver cirrhosis. Material and Methods: Thirty five patients with acute upper gastrointestinal bleeding (cirrhosis n=14, non-cirrhosis n=21) were evaluated over a 6 day period. The control cohort consisted of 100 blood donors. Serum concentrations of total, LDL (low-density lipoprotein) and HDL (high-density lipoprotein) cholesterol were measured enzymatically. Sterol concentrations were analysed using gas chromatography, data were statistically analysed. Results: In all patients, we found lower plasma levels of total cholesterol (P Conclusion: Our results showed substantial abnormalities in the cholesterol plasma profile including both the processes of cholesterol acquisition in patients with upper acute gastrointestinal bleeding. The patients with or without liver cirrhosis had similar trends in cholesterol plasma levels. Depression of cholesterol synthesis was, however, prolonged in the cirrhotic group and the data also suggest a different phytosterol metabolism.
Keywords: acute gastrointestinal bleeding; lipids; cholesterol; hypocholesterolemia; non-cholesterol sterols; phytosterols; liver cirrhosis